THE REALIZATION OF THE SPEECH ACT OF “COMFORTING” IN THE ENGLISH DISCOURSE: COMMUNICATIVE AND PRAGMATIC ASPECTS - Гедз, Світлана (Current Issues of Foreign Philology, 2021)
This article is dedicated to the investigation of verbal and nonverbal means of performing the speech act of “comforting” in the English language. The speech act of “comforting” is represented by the number of the speech moves aimed at the change of the addressee’s emotional behaviour in order to help him to overcome some negative emotions and feelings. The study shows that for succeeding the communicative intention the speaker makes use of various lexical and semantic means including such interjections as “Come. Come”, “there, there” and vocatives my dear, my love, darling. For comforting the addressee the sender utilizes the imperatives in both affirmative and negative forms, e.g. “Cheer up!”, “Don’t worry (about it)”, “Don’t let it get you down”. Such imperatives are referred to “polite imperatives”. The research states that constatives with the illocutionary effect of commissives may be the effective means of making an influence on the addressee in order to comfort him. The sender may also use the utterances with the illocutionary effect of menace. Performing the speech act of “comforting” the sender focuses the addresse’s attention not only on the beneficial side of the action which is suggested to him but also on the possible negative consequences if it is not accepted. The main types of communicative activity in this situation are persuading, focusing the addressee’s attention on personal experiences of those who were in the similar situation and the use of proverbs which embody people’s philosophy and psychology.